Feasibility Evaluation of an Android-based Nutrition App (Dietducate) Among Nutritionists Using the User Version of The Mobile Apps Rating Scale (uMARS) - Muhammad Iqbal; Elita Dwi Nurrahmawati; Husin Husin (Jurnal Teknologi Informasi dan Multimedia, 2023)
Online nutrition consultations are one of the strategic measures utilized to address complex nutritional issues. The use of smartphones in Indonesia is on the rise, particularly smartphones with the Android operating system. Indonesia has entered the 4.0 Industrial Revolution, which involves the application of technology in a variety of fields, including the healthcare industry. One application of this technology is the creation of the android application "dietducate." Using the uMARS (End-User Version of The Mobile Apps Rating Scale) method, this study aims to assess the feasibility of the android-based health application "dietducate" for nutritionists. Utilizing the uMARS research method and a 5-point scale, the research design is quantitative. Using a technique of purposive sampling, up to 35 nutritionists were gathered as subjects. The application evaluation was conducted using the uMARS questionnaire. The results indicated that the application quality score was within the acceptable range (4.05 out of 5). The component outcomes are determined by four supporting factors: involvement, functionality, aesthetics, and information. The results of each score are 3.97, 4.03, 4.02, and 4.23, respectively. It can be concluded that nutritionists can utilize the dietducate application. This app is also regarded as user-friendly and efficient for completing nutritionists' work. However, there are too many advertisements and minor bugs that need fixing to optimize app performance.